2016
DOI: 10.1136/bmjopen-2016-011394
|View full text |Cite
|
Sign up to set email alerts
|

Medication double-checking procedures in clinical practice: a cross-sectional survey of oncology nurses' experiences

Abstract: BackgroundDouble-checking is widely recommended as an essential method to prevent medication errors. However, prior research has shown that the concept of double-checking is not clearly defined, and that little is known about actual practice in oncology, for example, what kind of checking procedures are applied.ObjectiveTo study the practice of different double-checking procedures in chemotherapy administration and to explore nurses' experiences, for example, how often they actually find errors using a certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 30 publications
3
34
0
1
Order By: Relevance
“…Similar approaches that use electronic checking approaches where the staff member is checking with a computer may provide some relief if used within the regulatory requirements of the health services. Further, a recent study of double checking practices of oncology nurses has highlighted that there is evidence of jointly double-checking medications rather than independent checking of medications diminishing the benefits to patient safety (Schwappach et al 2016). The high frequency of interruptions during this joint double-checking process was particularly problematic in our study (Schwappach et al 2016).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Similar approaches that use electronic checking approaches where the staff member is checking with a computer may provide some relief if used within the regulatory requirements of the health services. Further, a recent study of double checking practices of oncology nurses has highlighted that there is evidence of jointly double-checking medications rather than independent checking of medications diminishing the benefits to patient safety (Schwappach et al 2016). The high frequency of interruptions during this joint double-checking process was particularly problematic in our study (Schwappach et al 2016).…”
Section: Discussionmentioning
confidence: 71%
“…Further, a recent study of double checking practices of oncology nurses has highlighted that there is evidence of jointly double‐checking medications rather than independent checking of medications diminishing the benefits to patient safety (Schwappach et al . ). The high frequency of interruptions during this joint double‐checking process was particularly problematic in our study (Schwappach et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Most studies reported that the double check process is poorly defined and that many variations of the double check process are executed in hospitals (Dickinson et al, 2010;Kellett and Gottwald, 2015). One detailed process description is the read-read back method from (Schwappach et al, 2016): one nurse reads out loud the medication order and another nurse verifies this on the medication label and vice versa. However, this study is different from ours since it is conducted on an oncology ward and focused on chemotherapy, and the role of the barcode scanner is unclear in the various scenario's.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies focused only on compliance and the absence of the double check (Alemanni et al, 2010;Alsulami et al, 2014;Schwappach et al, 2016;Sheu et al, 2009), extra understanding is needed about how nurses actually conduct the double check proceeding in everyday clinical practice. After all, most of the work seems to be carried out safely and without harming patients.…”
Section: Introductionmentioning
confidence: 99%